Ответы и объяснения

Лучший Ответ!
2013-08-19T19:59:46+00:00
По действиям:
а).
1) \frac{1- \sqrt{10} }{ \sqrt{2}+ \sqrt{5}}=  \frac{(1- \sqrt{10})(\sqrt{2}-\sqrt{5}) }{2- 5}=-\frac{1}{3}( \sqrt{2}- \sqrt{5}- \sqrt{2} \sqrt{10}+ \sqrt{5} \sqrt{10})=

=- \frac{1}{3}( \sqrt{2}- \sqrt{5}- 2\sqrt{5}+ 5\sqrt{2})=- \frac{1}{3}( 6\sqrt{2}- 3\sqrt{5})=-2 \sqrt{2}+ \sqrt{5}

2)  \frac{7}{2 \sqrt{2}+1}=  \frac{7(2 \sqrt{2}-1)}{4*2-1}=2 \sqrt{2}-1

3) (11-5 \sqrt{5})(2+ \sqrt{5})=22+11 \sqrt{5}-10 \sqrt{5}-5*5= \sqrt{5}-3

4) -2 \sqrt{2}+ \sqrt{5}+2 \sqrt{2}-1- \sqrt{5}+3=2

Ответ: 2.


б)
1)0,25( \sqrt{21}-5 )( \sqrt{7}+3 \sqrt{3})= \frac{1}{4}(\sqrt{7}\sqrt{21}+3 \sqrt{3} \sqrt{21}-5 \sqrt{7}-15 \sqrt{3})=

= \frac{1}{4}(7\sqrt{3}+9 \sqrt{7}-5 \sqrt{7}-15 \sqrt{3})= \frac{1}{4}(4\sqrt{7}-8 \sqrt{3})=  \sqrt{7}-2 \sqrt{3}

2)  \frac{2 \sqrt{7}-4}{1+ \sqrt{7} }=  \frac{(2 \sqrt{7}-4)(1- \sqrt{7} )}{1-7 }=- \frac{1}{6}(2 \sqrt{7}-2*7-4+4 \sqrt{7} ) =

=- \frac{1}{6}(6 \sqrt{7}-18 )=-  \sqrt{7}+3

3) 2 \sqrt{3}+ \sqrt{7}-2 \sqrt{3} - \sqrt{7} +3=3

Ответ: 3